2013
DOI: 10.1007/s12035-013-8479-6
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of the Development of Alzheimer’s Disease in Amyloid Beta-Infused Peroxiredoxin 6 Overexpression Transgenic Mice

Abstract: The amyloid beta (Aβ) peptide in the brains of patients with Alzheimer's disease (AD) is cytotoxic to neurons and has a central role in the pathogenesis of the disease. Peroxiredoxin 6 (Prdx6) is an antioxidant protein and could act as a cytoprotective protein. However, the role of Prdx6 in neurodegenerative disease has not been studied. Thus, the roles and action mechanisms in the development of AD were examined. Aβ1-42-induced memory impairment in Prdx6 transgenic mice was worse than C57BL/6 mice, and the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 52 publications
1
26
0
1
Order By: Relevance
“…42 In contrast, it has been suggested that the overexpression of PRDX6 could accelerate the development of AD. 43 Taking together the ability of PTN to protect against the neurotoxic effects of cocaine 6,8 and that, independently of the treatment, PTN-Tg mice show reduced levels of PRDX6 compared to WT mice, the data suggest that phosphorylation of PRDX6 may be suppressed in a step downstream of the signaling pathways triggered by PTN for this cytokine to exert its neurotrophic effects. All in all, in this case it is crucial to know the influence of tyrosine phosphorylation on the activity of the protein bacause PRDX6 is a 44 the phosphorylation of threonine in position 177 results in an activation of the phospholipase A 2 activity of PRDX6, 45 and it has been described that phospholipases A 2 increase during neurodegeneration.…”
Section: ■ Discussionmentioning
confidence: 95%
“…42 In contrast, it has been suggested that the overexpression of PRDX6 could accelerate the development of AD. 43 Taking together the ability of PTN to protect against the neurotoxic effects of cocaine 6,8 and that, independently of the treatment, PTN-Tg mice show reduced levels of PRDX6 compared to WT mice, the data suggest that phosphorylation of PRDX6 may be suppressed in a step downstream of the signaling pathways triggered by PTN for this cytokine to exert its neurotrophic effects. All in all, in this case it is crucial to know the influence of tyrosine phosphorylation on the activity of the protein bacause PRDX6 is a 44 the phosphorylation of threonine in position 177 results in an activation of the phospholipase A 2 activity of PRDX6, 45 and it has been described that phospholipases A 2 increase during neurodegeneration.…”
Section: ■ Discussionmentioning
confidence: 95%
“…Overexpression of Prdx6 protected against neuropathology in a mouse model of prion disease www.jlr.org Downloaded from (151). Although the assays for Prdx6-PLA 2 activity in these studies were not definitive, the administration of MJ33 provided evidence that the adverse effects of Prdx6 in these models might have reflected an increase in the aiPLA 2 activity in specific brain cells.…”
Section: Diseases Of the Central Nervous System (Cns)mentioning
confidence: 87%
“…Prx 6 is primarily expressed in astrocytes (Table 1); (Power et al, 2008) but is up-regulated in activated microglia and macrophages. This correlates with increased expression levels in Alzheimer's disease, and in Prx 6-overexpressing mice, the progression of memory impairment and CNS pathology of Alzheimer disease models is accelerated due to increased oxidative stress (Yun et al, 2013). The mechanism is still under elucidation, but it is interesting to note that the PLA 2 activity of Prx 6 enhances NOX2 activity, which depends on arachidonic acid for p47phox mobilization (Dana et al, 1998), in alveolar macrophages (Chatterjee et al, 2011) and other cell types (Ellison et al, 2012).…”
mentioning
confidence: 97%